2013
DOI: 10.1080/17451000.2013.810752
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and food selectivity of sprat (Sprattus sprattus) in Hardangerfjord, Norway

Abstract: The diet composition and prey selection of sprat (Sprattus sprattus) was studied in the Hardangerfjord, western Norway during four cruises in spring and autumn of 2009 and 2010. Feeding activity, indicated by stomach fullness, varied with sprat size, season and time of day. Small-sized sprat were found to feed both in spring and autumn, while the larger individuals had lower feeding activity late in the season. Diurnal variation in stomach fullness was observed in the autumn but not in spring. Sprat fed on a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…For example, copepods were found to be among the most important prey of sprat in Hardangerfjord. The numerically most important food species for sprat in the Hardangerfjord was the planktonic harpacticoid copepod Microsetella norvegica (Falkenhaug and Dalpadado, 2014). This is in agreement with previous studies on sprat from the North Sea (De Silva, 1973;Last, 1987;Voss et al, 2009) and the Baltic Sea (Arrhenius, 1996;Möllmann et al, 2004;Casini et al, 2004).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…For example, copepods were found to be among the most important prey of sprat in Hardangerfjord. The numerically most important food species for sprat in the Hardangerfjord was the planktonic harpacticoid copepod Microsetella norvegica (Falkenhaug and Dalpadado, 2014). This is in agreement with previous studies on sprat from the North Sea (De Silva, 1973;Last, 1987;Voss et al, 2009) and the Baltic Sea (Arrhenius, 1996;Möllmann et al, 2004;Casini et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…Depending on the trophic controls forming upwards from the lowest level and downwards from the highest level of the food chain, long-term changes in fish stocks and leaps between low and high stock regimes can be identified (Daskalov, 2002). Although there are a large number of articles related to the feeding ecology of sprat in the Baltic (Arrhenius, 1996;Möllmann et al, 2004;Casini et al, 2004;Baumann et al, 2007) and the North Sea (Last, 1987;Voss et al, 2009;Falkenhaug and Dalpadado, 2014). Unfortunately, the number of studies on the biological properties of this species found in Turkish coast is limeted (Avşar, 1994;Şahin, 1999) and there is not any study available on its diet composition.…”
Section: Introductionmentioning
confidence: 99%
“…Protected fjords could also provide a favourable habitat in the sense that M. leidyi tends to avoid turbulent waters, possibly due to the ambient fluid motion interfering with its feeding currents (Mianzan et al, 2010;Sutherland et al, 2014). In terms of food availability, mesozooplankton concentrations in inner Hardangerfjord are equivalent tõ 2-9.5 mg C m 23 in the spring, with patches of 8-14 mg C m 23 found in autumn and winter (Falkenhaug & Dalpadado, 2014). The predatory ctenophore Beroe cucumis is also known to inhabit fjord basins year round, potentially limiting the survival of overwintering lobates (Falkenhaug, 1996).…”
Section: Source -Sink Dynamicsmentioning
confidence: 99%
“…) may be present in inner fjord areas during autumn and winter (Falkenhaug & Dalpadado, 2014), making these areas mnemiopsis leidyi in norway…”
mentioning
confidence: 99%
“…Sprat, in contrast, is known as a strict selective/ particulate feeder that usually do not filterfeed (Bernreuther 2008;Mӧllmann et al 2004), apart from at low light intensities (Bernreuther et al 2013) or high turbidity (Falkenhaug and Dalpadado 2014). Visibility is the best explanation for preferring later stages of egg development for both sprat and herring, which is consistent with previous studies conducted in the Baltic Sea (Bernreuther et al 2013;Wieland and Köster 1996) as well as in the North Sea (Thompson and Riley 1981;Segers et al 2007) and the Irish Sea (Ellis and Nash 1997).…”
Section: Selectivity Of Egg Development Stagesmentioning
confidence: 99%